Presse, profesjon og politikk Festskrift til Paul Bjerke - Fonn, Birgitte Kjos; Lexerød Hovlid, Ellen; Mathisen, Birgit Røe (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Press, Profession and Politics is a festschrift in honor of Paul Bjerke, who celebrated his 70th birthday on 2 October 2022. Bjerke has had a far-reaching career in journalism, research and as a social commentator. This festschrift consists of research articles, professional literature, and congratulatory texts from colleagues and collaborators in the media and academic communities. The anthology includes new analyses of various aspects of professional journalistic practice and reflections on the realities of journalism today. Three key concepts are central to an understanding of Paul Bjerke's research work: press, profession and politics. These concepts comprise the title of the festschrift and are also used to structure its content, with the goal in mind of providing insight into some of the work Bjerke has contributed, as well as linking the texts in this anthology to his research activities. In addition, we gain insight into his many years as a journalist, news editor, and finally, the editor of Klassekampen. This book will be of interest to media researchers and researchers in other disciplines concerned with the function of the media in society, as well as students and practitioners.